Superovulatory responsiveness and embryonic development in Iranian Afshari ewes treated with two different concentrations of bovine somatotropin - SAFDAR, AMIR HOSSEIN ASGARI (The Indian Journal of Animal Sciences, 2016)
Bovine somatotropin (bST) was administered @ 50 and 100 mg at the beginning of the estrus synchronization and natural mating of the sheep to evaluate the improvement of the ovulation rate, embryonic development and pregnancy rate of the transferred embryos. Donors (48) were treated with 3 different types of treatment; group A (15): treated with bST-100, received 100 mg of bST at the beginning of the synchronization and natural mating, group B (15): treated with 50 mg of bST same as the previous group and control (18) did not receive any type of bST. Each recipient (108) received 2 embryos: 30 recipients received embryos from bST-100s, 45 received the embryos from bST-50 and 33 received embryos from the control group. Using SAS related GENMOD method, superovulatory response, embryo recovery, cleavage rate, transferable embryo percentage, quality of embryos, rates of pregnancy and embryonic development were analyzed. Using GLM procedure, numbers of corpus luteum and blastocyst cells were analyzed. The results showed that bST administration had no significant effect on superovulatory response, number of CL and recovered structures. Number of transferable embryos and embryos that had reached to the blastocyst in bST-50 was more than bST-100 and control group. In conclusion, treatment 50 mg bovine somatotropins enhance the ratio and growth of the transferable embryos. Embryos of bST-50 treatment indicated an improved embryonic development but bST did not affect the pregnancy rates of transferred embryos.